CAUSES OF SOIL EROSION IN UZBEKISTAN AND FACTORS AFFECTING EROSION (Scientific journal of the Fergana State University, 2024)
Uzbekistan, a landlocked country in Central Asia, faces significant soil erosion challenges driven by various natural and anthropogenic factors. The issues of soil erosion protection are becoming a global problem in the world and in Uzbekistan. With its predominantly arid to semi-arid climate, extensive agricultural practices, and limited water resources, the country is particularly susceptible to soil erosion. In this article, we will examine the problems of soil erosion in Uzbekistan, their causes, effects, and efforts to solve this important environmental problem.